Hedgehog Signaling Promotes the Proliferation and Subsequent Hair Cell Formation of Progenitor Cells in the Neonatal Mouse Cochlea - Chen, Yan (Front Mol Neurosci, 2017)
Hair cell (HC) loss is the major cause of permanent sensorineural hearing loss in mammals. Unlike lower vertebrates, mammalian cochlear HCs cannot regenerate spontaneously after damage, although the vestibular system does maintain limited HC regeneration capacity. Thus HC regeneration from the damaged sensory epithelium has been one of the main areas of research in the field of hearing restoration. Hedgehog signaling plays important roles during the embryonic development of the inner ear, and it is involved in progenitor cell proliferation and differentiation as well as the cell fate decision. In this study, we show that recombinant Sonic Hedgehog (Shh) protein effectively promotes sphere formation, proliferation, and differentiation of Lgr5+ progenitor cells isolated from the neonatal mouse cochlea. To further explore this, we determined the effect of Hedgehog signaling on cell proliferation and HC regeneration in cultured cochlear explant from transgenic R26-SmoM2 mice that constitutively activate Hedgehog signaling in the supporting cells of the cochlea. Without neomycin treatment, up-regulation of Hedgehog signaling did not significantly promote cell proliferation or new HC formation. However, after injury to the sensory epithelium by neomycin treatment, the over-activation of Hedgehog signaling led to significant supporting cell proliferation and HC regeneration in the cochlear epithelium explants. RNA sequencing and real-time PCR were used to compare the transcripts of the cochleae from control mice and R26-SmoM2 mice, and multiple genes involved in the proliferation and differentiation processes were identified. This study has important implications for the treatment of sensorineural hearing loss by manipulating the Hedgehog signaling pathway.